Policy Evaluation Total Quality Management (TQM) School Applying International Organization for Standardization (ISO) in the City of Samarinda - Azainil Azainil; Nurul Ulfa Apriliani; Suandie Suandie (Journal of Educational Review and Research, 2018)
This policy evaluation research to find out the need, implementation and achievement result of TQM in Vocational High School applying ISO.This research is a policy evaluation research, with qualitative research method. Qualitative research method is a research method used to determine natural condition (naturalistic), where the researchers are as a key instrument, data technique in triangulation. Data analysis with inductive and more.This policy evaluation study examines the TQM policy documents required for schools implementing the ISO. The evaluation model uses the Context, Input, Process and Product (CIPP) model developed by Stuffebeam. Component Criteria. From the vision statement. The input components of the curriculum, financing, facilities and infrastructure, educators and educators as well as students, curriculum preparation process components, teaching materials, teaching and learning process and assessment, while product / output components of student satisfaction, student achievement and school performance implements TQM ISO.Research result. TQM ISO-based schools need to be implemented, both schools have the formulation of vision, mission, goals and restra. The input components of all schools have implemented the 2013 curriculum, discipline, sufficient facilities and infrastructure, educators and educators are in accordance with standards and there are standards of acceptance. The process component shows all teachers have been preparing syllabus, lesson plan and teaching materials, and teaching and learning process and assessment according to the standard. Existing Product / Outputs. Students, student achievement and achievement in applying ISO 9001-2008 well.Suggestions of these results are (1) improvements from the TQM ISO understanding for all stakeholders, (2) need also from the same language, and (3) improve the ISO-based TQM with commitment improvement, paradigm shift, mental attitude and organizing the guarantee system quality.